À la recherche d’une poétique ou comment lire une chanson populaire américaine - Frédéric Sylvanise (Itinéraires)
Following the example of what cantology does with French songs, it seems important to us to elaborate a method meant to analyse American popular songs which would take into account the music, the lyrics and voices equally. Technology, defined as a specific use of studio recording techniques, will also matter. Indeed neither musicology nor Anglo-Saxon cultural studies have exhausted the subject of the poetics of songs, meaning the study of a finished system comparable to a text with multiple entries in which none of the elements would prevail over the others in terms of status. Some song extracts will be examined in order to illustrate our remarks.